Narrative Literature Review: Implications of the Role of School Cooperatives in Fostering Entrepreneurial Spirit - Ratumbuysang, Monry Fraick Nicky Gillian; Supriyanto, Supriyanto; Hasanah, Mahmudah; Bahar, Syarifuddin (Journal of Economics Education and Entrepreneurship, 2026)
Poverty remains a major challenge faced by many countries, particularly in developing nations where economic inequality and limited employment opportunities persist. To address this issue, governments have implemented various strategies aimed at strengthening economic capacity and fostering entrepreneurial mindsets within society. One such strategy is the development of cooperatives, which are economic institutions based on the principles of kinship, mutual cooperation, and economic democracy. The purpose of this study is to examine the role of school cooperatives in fostering the entrepreneurial spirit among students. Specifically, this study explores how involvement in school cooperative activities contributes to the development of students’ entrepreneurial attitudes, skills, and values. This study employs a narrative literature review with a structured search and screening process. Relevant articles were identified through academic databases using keywords related to school cooperatives and student entrepreneurship. The selection process involved reviewing titles, abstracts, and full texts to ensure their relevance to the research objective. A total of twenty articles that met the inclusion criteria were selected and analyzed. The findings from these studies were then synthesized to identify patterns and key themes related to the contribution of school cooperatives to entrepreneurial development. The findings indicate that school cooperatives can foster students’ entrepreneurial spirit through several mechanisms. These include experiential learning opportunities, the development of responsibility and leadership through cooperative management activities, and the improvement of financial literacy through basic financial management practices. In addition, participation in cooperative activities helps cultivate a strong work ethic and collaborative skills among students. The study implies that strengthening school cooperatives can be an effective strategy for integrating entrepreneurship education with practical learning experiences in schools.